1999
DOI: 10.1172/jci5183
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin deficiency exacerbates experimental glomerulonephritis: a protective role for endothelial P-selectin in inflammation

Abstract: P-selectin is a leukocyte adhesion receptor present in endothelial cells and platelets. We examined the role of P-selectin in the autologous phase of an accelerated model of anti-glomerular basement membrane (GBM) glomerulonephritis using P-selectin-deficient mice and chimeric mice expressing P-selectin only in platelets or endothelial cells. P-selectin-deficient mice exhibited more severe glomerular damage with increased interstitial mononuclear leukocytic infiltrates, and had significantly increased proteinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 47 publications
5
123
0
Order By: Relevance
“…Indeed, VCAM-1 has been suggested as a potential therapeutic target in end-organ disease (30,31), although antibody-mediated blocking in experimental immune nephritis has not been very effective (32). Likewise, it has been suggested that glomerular VCAM-1, P-SELECTIN, TNFRI, AND CXCL16 IN NEPHRITIC URINEdisease may be amenable to therapy by blocking P-selectin (16), although conflicting results have been noted in experimental immune nephritis (37). Based on the antibody-blocking studies described here, CXCL16 may turn out to be yet another therapeutic target in immune nephritis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Indeed, VCAM-1 has been suggested as a potential therapeutic target in end-organ disease (30,31), although antibody-mediated blocking in experimental immune nephritis has not been very effective (32). Likewise, it has been suggested that glomerular VCAM-1, P-SELECTIN, TNFRI, AND CXCL16 IN NEPHRITIC URINEdisease may be amenable to therapy by blocking P-selectin (16), although conflicting results have been noted in experimental immune nephritis (37). Based on the antibody-blocking studies described here, CXCL16 may turn out to be yet another therapeutic target in immune nephritis.…”
Section: Discussionmentioning
confidence: 88%
“…P-selectin is an adhesion molecule that is expressed on platelets and several other cell types, and the level of P-selectin has been reported to be elevated in other autoinflammatory diseases, in which it has also been recognized as a circulating disease marker (11)(12)(13). The prominence of P-selectin in experimentally induced immune nephritis has also been quite extensively studied (34)(35)(36)(37). Interestingly, a protective role for endothelial P-selectin in immune nephritis has been suggested (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Serum urea, serum calcium, and serum phosphate levels were measured with standard laboratory techniques. The glucose tolerance test was performed at the age of 7 weeks and the insulin tolerance test at the age of 15 weeks.…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…23 In another mouse model of glomerulonephritis, P-Selectin-deficient mice show increased proteinuria, glomerular damage and mortality. 24 However, although these animal models have the potential to provide a link between decreased production of P-Selectin and increased risk of renal disease, there may be a complication in the interpretation the results. This complication was first identified by Bygrave et al, who discovered that the 129-derived chromosome 1 segment used for gene-targeted deletions may itself produce symptoms of autoimmunity.…”
Section: Meta-analysismentioning
confidence: 99%